Análise numérica por acoplamento hidromecânico de Ensaios de laboratório e de campo em solos não saturados. - Balreira, David Sena (2022)
The objective of this dissertation consists of numerical simulation of edometric tests, plate and surface foundations run on unsaturated soils, where the suction effect, adopts an elastoplastic behavior and uses coupling hydromechanical in the analyses. To carry out the analysis of the hydromechanical behavior, in the methodology is considered in the modeling an approach with the simultaneous influence of the phenomena of equilibrium and hydraulics in porous, saturated and unsaturated media. Comparisons were made between the results of numerical and experimental simulation of the tests carried out in soils from Campo Novo do Parecis, in Mato Grosso, from Fortaleza and Morada Nova in Ceará. The simulations showed good results that showed agreement with the experimental data, realistically validating the modeling numerical hydromechanics of unsaturated soils with elastoplastic behavior. In especially for unsaturated soils with collapsible behavior, the model shows important results, since it considers the variation of the stiffness and the expansion of the elastic behavior with suction, as well as the prediction of sudden deformations when the specimens are flooded and in the field. It was still possible to get results that take into account soil expansion in the vicinity of a running shoe. The model used in the numerical simulations is the Barcelona Basic Model (BBM), proposed by Alonso, Gens and Josa, 1990 which is implemented in the CODE- _BRIGHT.